The Effectiveness of Early Vacancy Information in the Presence of Monitoring and ALMP - Ricarda Schmidl (Institute for the Study of Labor (IZA), 2015)
This paper studies the effectiveness of vacancy information from the public employment services (PES) in Germany, focussing on vacancy information obtained early in the unemployment spell. As in many other countries, the German activation practice combines information provision with monitoring to increase the willingness to apply. In case of a failed application, unemployed may participate in more intensive active labor market programs (ALMP). Exposure to monitoring or participation in ALMP is likely to confound the effect of information; our aim is to disentangle the different effects. Based on a flexible propensity score matching approach, we find that vacancy information increases the entry rate into unemployment predominantly by jobs mediated via the PES. Monitoring seems to reinforce this effect while limiting the crowding out of transitions made through other channels. In case of continued unemployment, early vacancy information reduces the participation rate in ALMP for some labor market groups. This is however not found to mediate the effect on employment transitions. We hence suggest that early vacancy information may increase the cost-effectiveness of the overall activation process even in the case of unsuccessful applications. Slight negative effects on employment quality seem to be driven by a combination of vacancy quality and monitoring.
Keywords: J08; J64; 330; unemployment; vacancy information; public employment services; active labor market programs